2009
DOI: 10.1038/cr.2009.68
|View full text |Cite
|
Sign up to set email alerts
|

RUVBL2, a novel AS160-binding protein, regulates insulin-stimulated GLUT4 translocation

Abstract: In fat and muscle cells, insulin-stimulated glucose uptake is mainly mediated by glucose transporter 4 (GLUT4), which translocates from intracellular compartments to the cell surface in response to insulin stimulation. AS160 is one of the substrates of Akt and plays important roles in insulin-regulated GLUT4 translocation. In this study, RuvBlike protein 2 (RUVBL2) is identified as a new AS160-binding protein using mammalian tandem affinity purification (TAP) combined with mass spectrometry. In 3T3-L1 adipocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…This indicates that Reptin silencing increases the sensitivity of HCC cells to insulin, and conversely that the high level of Reptin found in HCC cells likely participates to insulin resistance, a known promoting factor for HCC development . To our knowledge, the regulation of insulin signalling by Reptin in mammalian cells has been so far addressed only in a single study, performed in murine adipocytes, which showed that Reptin silencing reduced the phosphorylation of the Akt substrate AS160, although Akt phosphorylation itself was not examined . This result is opposite to the findings we report here in several HCC cell lines and might be explained by cell‐specific events.…”
Section: Discussioncontrasting
confidence: 99%
“…This indicates that Reptin silencing increases the sensitivity of HCC cells to insulin, and conversely that the high level of Reptin found in HCC cells likely participates to insulin resistance, a known promoting factor for HCC development . To our knowledge, the regulation of insulin signalling by Reptin in mammalian cells has been so far addressed only in a single study, performed in murine adipocytes, which showed that Reptin silencing reduced the phosphorylation of the Akt substrate AS160, although Akt phosphorylation itself was not examined . This result is opposite to the findings we report here in several HCC cell lines and might be explained by cell‐specific events.…”
Section: Discussioncontrasting
confidence: 99%
“…Further studies on RuvBs confirmed their involvement in multiple cellular pathways such as cell cycle progression and RNA polymerase IIdirected transcription [8], DNA damage response, replication fork reversal [9], nonsense-mediated mRNA decay [10], insulin stimulated GLUT4 translocation [11], small nucleolar ribonucleotide protein (snoRNPs) assembly [12], cellular transformation, cancer metastasis, apoptosis, mitosis, and development [13,14]. RuvBs are essential components of several complexes of diverse role and it is expected that their mode of function was very similar in these wide range of complexes [14].…”
mentioning
confidence: 72%
“…This may further support the idea that TBC1D1 could compensate for the loss of TBC1D4 S711 phosphorylation in the TBC1D4-S711A-expressing muscles. 7,18,28,29,42), and it is possible that the "signature" phosphorylation patterns induced by upstream kinases on TBC1D1 and TBC1D4 result in differential binding of these partners and thereby distinct regulation of Rab-GAP activity. Similar Rab specificity is likely due to the high homology between TBC1D1 and TBC1D4, especially in the GAP domain of the proteins (30).…”
Section: Discussionmentioning
confidence: 99%